IMPROVING STUDENTS VOCABULARY BY USING WORD GAME APPLICATION - Umbola, Hertila; Maru, Mister G.; Hampp, Paula (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This study aims to prove whether the Word Game Application which is Wordscapes can help students to improve their vocabulary or not In this study the researcher employed the quantitative research method The subject of this study is class X J at SMA N 1 Kotamobagu which consists of 30 students 13 are boys and 17 are girls with an average age of 15 17 years old Data were collected using pre test and post test design in the form of matching tests The result of this study proves that the mean scores of the post test are higher than the mean scores of the pre test The mean scores of the pre test is 63 16 and the mean scores of post test is 85 83 Based on the results obtained it can be concluded that the Word Game Application which is Wordscapes can help students to improve their vocabulary mastery and make students more enthusiastic in learning < p>